Sliding Mode Controller Design With Optimized PID Sliding Surface Using Particle Swarm Algorithm - Chong, Chee Soon; Ghazali, Rozaimi; Jaafar, Hazriq Izzuan; Syed Hussien, Sharifah Yuslinda (Elsevier B.V., 2017)
This article deals with an evaluation on the designed controller named as sliding mode control (SMC) which sliding surface of the controller has been integrated with proportional-integral-derivative (PID) controller. The control scheme is established from the derived dynamic equation which stability is proven through Lyapunov theorem. In the performance assessment on the designed PID sliding surface, the controller parameter is first obtained through conventional tuning method known as Ziegler-Nichols (ZN), which is then compared with the particle swarm optimization (PSO) computational tuning algorithm. From the observation of the simulation results, the PSO tuning algorithm showing outperform performances compared to the conventional ZN tuning method in term of trajectory tracking on the electro-hydraulic actuator (EHA) system.